Gender differences in career progression: Does the effect of children capture low work effort? - Astrid Kunze (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This study exploits longitudinal employer-employee matched data to investigate gender differences in the probability to climb the job ladder with focus on the effect of children. We attempt to disentangle whether children directly affect promotions, or whether the effect of children is correlated with effort. We find that the probability to progress on the career ladder is decreased for women through children, but not for men. These effects are particularly strong at the lower and medium ranks. We explore whether the effect of children is correlated with several proxies of work effort including whether workers are highly attached or not, hours of work, and relative bonus payments. In promotion regressions controllling for these factors we find that the effects of children remain unchanged quantitatively as well qualitatively. If we compare workers with high effort levels above the 60th residual earnings percentile, we find large gender differences in promotion probabilities and it is men with 1-2 children who are most likely to be climb the career ladder.
Keywords: J12; J24; J62; 330